Factors Associated with Teenage Pregnancy: A Hospital-Based Case-Control Study (Journal of Karnali Academy of Health Sciences, 2024)
Background: Teenage pregnancy is a major public health problem and is considered to be high risk for maternal health, pregnancy outcomes, and long-term effects. This study aims to determine the factors associated with teenage pregnancy among pregnant teenagers and non-teenagers in a tertiary hospital of Nepal.Methods: A hospital-based case-control study was conducted using 1:2 case-control ratio among 109 pregnant teenagers and 218 non-teenage pregnant women attending antenatal service at a tertiary hospital of Rupandehi, Nepal, from October 2020 to February 2021. Two controls were selected on the same day when a case was identified. Variables found significance (p